2019
DOI: 10.1093/eurheartj/ehz786
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and cardiac fibrosis

Abstract: The understanding of atrial fibrillation (AF) evolved from a sole rhythm disturbance towards the complex concept of a cardiomyopathy based on arrhythmia substrates. There is evidence that atrial fibrosis can be visualized using late gadolinium enhancement cardiac magnetic resonance imaging and that it is a powerful predictor for the outcome of AF interventions. However, a strategy of an individual and fibrosis guided management of AF looks promising but results from prospective multicentre trials are pending. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(128 citation statements)
references
References 105 publications
3
119
1
5
Order By: Relevance
“…Several observations have led to new insights in AF management and arrhythmia‐associated cardiac remodeling. AF is a progressive disease that is not only a consequence of structural, hemodynamic, and electrophysiological remodeling, but also a cause of the same processes 4 . One of the markers of LA remodeling is the dilation of the atrial structure in AF patients, which was also found to be a positive predictor of AF/AT recurrence in our study.…”
Section: Discussionsupporting
confidence: 72%
“…Several observations have led to new insights in AF management and arrhythmia‐associated cardiac remodeling. AF is a progressive disease that is not only a consequence of structural, hemodynamic, and electrophysiological remodeling, but also a cause of the same processes 4 . One of the markers of LA remodeling is the dilation of the atrial structure in AF patients, which was also found to be a positive predictor of AF/AT recurrence in our study.…”
Section: Discussionsupporting
confidence: 72%
“…It seems that patients with higher sphericity indexes have an 11 times higher risk of developing 1-year post-CA recurrences as compared to those with discoid LA [22]. In the LAGO-AF study, the LA sphericity index emerged as the sole independent predictor of recurrences [22][23][24]. Subsequently, geometrical structural remodelling may be superior to size in predicting CA outcomes and arrhythmia recurrences.…”
Section: Left Atrial Shapementioning
confidence: 99%
“…Late-gadolinium enhancement CMR (LGE-CMR) is the gold standard in assessing myocardial fibrosis [15,23]. A gadolinium-based contrast agent enhances fibrosis detection due to its accumulation in the extracellular space (increased in fibrotic tissues) and its delayed clearance.…”
Section: Left Atrial Fibrosismentioning
confidence: 99%
“…B. durch Wearables und Implantables) eine wichtige Rolle für individuelle Therapiekonzepte. (Nach [22], mit freundlicher Genehmigung von Oxford Academic)…”
Section: Abb 4 9 Personalisierteunclassified